Investigating conversational dynamics in triads: Effects of noise, hearing impairment, and hearing aids - Petersen, Eline Borch (Frontiers in Psychology, 2024)
Communication is an important part of everyday life and requires a rapid and coordinated interplay between interlocutors to ensure a successful conversation. Here we investigate whether increased communication difficulty caused by additional background noise, hearing impairment, and not providing adequate hearing-aid (HA) processing affected the dynamics of a group conversation between one hearing-impaired (HI) and two normal-hearing (NH) interlocutors. Free conversations were recorded from 25 triads communicating in low (50 dBC SPL) or high (75 dBC SPL) levels of canteen noise. In the conversations at low noise levels, the HI interlocutor was either unaided or aided. In the conversation at high noise levels, the HI interlocutors either experienced omnidirectional or directional sound processing. Results showed that HI interlocutors generally spoke more and initiated their turn faster, but with more variability, than the NH interlocutors. Increasing the noise level resulted in generally higher speech levels, but more so for the NH than for the HI interlocutors. Higher background noise also affected the HI interlocutors to speak in longer turns. When the HI interlocutors was unaided at low noise levels, both HI and NH interlocutors spoke louder, while receiving directional sound processing at high levels of noise only reduced the speech level of the HI interlocutor. In conclusion, noise, hearing impairment and hearing-aid processing mainly affected the speech levels, while the remaining measures of conversational dynamics (FTO median, FTO IQR, turn duration, speaking time) were unaffected. Hence, although experiencing large changes in the communication difficulty, the conversational dynamics of the free triadic conversations remain relatively stable.